An Analytical and Comparative Study of the Urdu, Sindhi, and English Translations of Nahj al-Balagha - Mr. Faseeh Hyder Shah; Dr. Mukhtiar Ahmed Kandhro; Dr. Nazia Begum (Journal of Religion and Society, 2026)
This study presents a comparative linguistic, rhetorical, and intellectual analysis of selected excerpts from Letter 53 of Nahj al-Balagha (Maktub-e-Malik al-Ashtar), with reference to its Arabic original and Urdu, Sindhi, and English translations. The research employs a comparative framework based on lexical, semantic, and stylistic dimensions to examine the process of meaning transfer across languages.Nahj al-Balagha occupies a central position in Islamic intellectual and literary heritage, and more than 300 translations and commentaries are reported in scholarly sources, highlighting its wide academic significance. The analysis shows that the Arabic text is highly concise, rhetorically powerful, and intellectually rich, making translation a complex interpretive task rather than a simple linguistic transfer. Among the examined versions, the Urdu translation is relatively closer to the original in meaning and structure, the Sindhi translation is clear but less rhetorically intensive due to indirect transmission, and the English translation simplifies some cultural and rhetorical nuances for global readability.The study concludes that no translation can fully reproduce the linguistic and rhetorical depth of Nahj al-Balagha, although direct translations supported by authoritative commentaries preserve its meaning more effectively. Keywords: Nahj al-Balagha; Imam Ali (A.S.); Linguistic Analysis; Rhetoric; Comparative Study; Translation Studies; Stylistics; Letter of Malik al-Ashtar